Boosting AgoshRNA activity by optimized 5'-terminal nucleotide selection. Issue 7 (3rd July 2019) - Gao, Zongliang; Berkhout, Ben; Herrera-Carrillo, Elena
ABSTRACT: RNA interference (RNAi) can be triggered by synthetic small interfering RNAs (siRNAs) or transgene-expressed short hairpin RNAs (shRNAs). Recent evidence indicates that shRNA molecules, with a relatively short stem and small loop, are processed by Argonaute 2 protein (Ago2). We named these molecules AgoshRNA as Ago2 is involved in both the processing and the subsequent mRNA-silencing reaction. This alternative processing route yields only a single guide strand, which thus avoids potential off-target effects induced by the passenger strand of a regular shRNA. We recently described that the introduction of a 5ʹ-terminal purine (A or G) and a mismatch at the bottom of the hairpin enhances the AgoshRNA activity. The critical 5ʹ-terminal nucleotide (nt) represents the +1 position of the transcriptional promoter, which influences the transcriptional efficiency and initiation accuracy as demonstrated for the H1 RNA polymerase (Pol) III promoter. These findings highlight the necessity of considering Pol III requirements in the design of optimized AgoshRNA cassettes. In this study, we report the design and expression of potent AgoshRNAs by two other popular Pol III promoters: U6 and 7SK, which were recently reported to have a distinct transcription profile compared to the H1 promoter. We propose general rules for the design and expression of potent AgoshRNA molecules using Pol III cassettes, which should augment the application of novel AgoshRNA reagents for basic research and therapeutic purposes.